WATER AND ENERGY IN SOUTH AFRICA – MANAGING SCARCITY - POTGIETER, Petrus H. (Journal of Environmental Management and Tourism, 2016)
In this paper we examine the nexus of water an energy scarcity in South Africa. The fresh water resources of the country are close to exhaustion (Business Day 2009, Turton 2008), yet safe drinking water is not yet universally available to all in the country – in spite of a government policy to provide water for basic needs, taken to be 25l per person per day (Coovadia et al. 2009, 817). A growing economy and a population now close to 50 million have also put considerable strain on the electricity supply and distribution system, including wide-spread residential power outages in the main economic centers and, since January 2008, mandatory cuts for industrial users (Patel 2008, 53). The paper provides an overview of the current system in South Africa for supplying and managing water and electricity – for residential, industrial and for agricultural use – with a special emphasis on the energy requirements for delivering water as well as the water required in generating electric power. Finally we consider the example of Australia, another country with severe water shortages and one with a comparable demand for electricity, and attempt to draw lessons for South Africa from Australia’s more market- driven approach to energy and water.